2013
DOI: 10.1136/emermed-2012-202166
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of the barriers to prehospital management of acute pain in children

Abstract: The pathway to improving care must include an emphasis on improvements in practitioner education and training, offering alternatives to assessing pain in preverbal children, exploring the intranasal route of drug delivery in managing acute severe pain, and robustly developed evidence-based guidelines that are practitioner friendly and patient-focused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 25 publications
2
54
0
1
Order By: Relevance
“…Emergency medical services (EMS) personnel report that the major challenges preventing or delaying the relief of acute pain during initial treatment include an inability to assess pain and fasting times, and a limited choice of agents and delivery routes. Variability in provider education and different beliefs have also been mentioned as barriers to providing this treatment, and they are potential areas of intervention [4,5]. These challenges, although present in the emergency department (ED), are even more pronounced in the prehospital setting and more marked in pediatric patients than in adults [6].…”
Section: Introductionmentioning
confidence: 98%
“…Emergency medical services (EMS) personnel report that the major challenges preventing or delaying the relief of acute pain during initial treatment include an inability to assess pain and fasting times, and a limited choice of agents and delivery routes. Variability in provider education and different beliefs have also been mentioned as barriers to providing this treatment, and they are potential areas of intervention [4,5]. These challenges, although present in the emergency department (ED), are even more pronounced in the prehospital setting and more marked in pediatric patients than in adults [6].…”
Section: Introductionmentioning
confidence: 98%
“…This novel barrier appears to be quite sizeable and will not be overcome without changing behavior among EMS leadership and emergency department staff, as well as making paramedics more confident in their decisions. Negative responses from ED staff was also endorsed as a factor affecting pediatric analgesic administration by paramedics in the qualitative study by Murphy et al 18 Our study described the prevalence of a number of barriers that have been previously reported, such as concern regarding the pain caused by intravenous catheter placement, allergic reactions to medication, and difficulty assessing pain in children. [14][15][16]18 A recent nationwide survey of EMS providers 20 and a survey study in Canada 21 also found assessment of pain in children to be a top knowledge gap and barrier to analgesic administration among providers.…”
Section: Discussionmentioning
confidence: 74%
“…Skill deficits include inability to obtain vascular access and concern about causing pain from intravenous catheter placement and medication injection. [14][15][16][17][18][19] A recently published hypothesis-generating qualitative study identified previously unrecognized barriers to and enablers for prehospital analgesic administration in children. 16 A novel barrier, termed unwanted attention from authority figures, was identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The paramedic's scope of practice includes the management of pain in vulnerable populations, such as those at extremes of age. However, children experiencing pain are at risk of inadequate analgesia because of age‐related communication problems, inadequate paramedic education in pain management and lack of experience in assessing and caring for the child experiencing pain …”
Section: Introductionmentioning
confidence: 99%